ANALISIS MODEL E-LEARNING DAN DAMPAKNYA TERHADAP KUALITAS SUMBER DAYA MANUSIA (SDM) - Christanto Edy, Irwan (ADVANCE, 2014)
In the world of education , the problems faced are the quality of human resources. Qualified human resources will give a great influence to the progress and prosperity of a nation . The Resource constraints often be a contributing faktor to the low quality of human resources in Indonesia . Therefore, researcher is interested in studying the correlational relationship education, quality of human resources and Internet technologies .The purpose of this study are to 1 ) determine the prototype model of e-learning software which is good for presenting information quality learning, 2 ) knowing a good model that describes the implementation of e-learning in educational institutions, 3 ) determine the theoretical models that describe the relationship of adoption internet-based information technology, namely e-learning on the quality of iterative learning systems and quality impact on improving the quality of Human Resources ( HR ). To achieve the research objectives , this study uses the approach 1 ) model of information system design e-learning , 2 ) Qualitative and 3 ) quantitative , with a sample size of 100 respondents obtained from students throughout the province of Central Java , and instruments which is used to pull the questionnaire . The pattern of the questionnaires using a Likert scale with five alternative answers . The data analysis technique used is the index number to describe each study variable and SEM analysis to determine causal relationships between variables. Before SEM analysis instrument used to test the assumption is valid and reliable .The results showed that : 1 ) Model Internet-based learning system that e-learning provides significant effect on improving the quality of learning and the impact on the quality of human resource , 2 ) model is Internet based learning system is an e-learning system has more value than any other study is in create interaction between teachers and learners more effectively. Communication that occurs can occur without being limited geographic area and time . Learners can be discussions, tasks , answer questions , access learning materials at any time without limited time and regions, 3 ) model based learning system that internet e-learning provides significant effect on improving the quality of human resources, where the quality of the learning part that can not be separated from the quality of human resources. Keywords : learning, quality, human resources